Market Leaders’ Tax-Motivated Income Shifting and U.S. Domestic Firms’ Investment Efficiency - Nessa, Michelle L.; Tang, Xinjie; Wilson, Ryan J. (The Accounting Review, 2026)
ABSTRACT This paper examines whether U.S. domestic firms’ investment decisions are affected by their expectations of market leaders’ tax-motivated income shifting. Market leaders’ financial reports can help peers evaluate industry conditions and potential investment payoffs, but income shifting obscures the geographic source of profits and reduces the informativeness of these disclosures. Thus, when peers expect that leaders shift income, they face greater uncertainty about the outcomes of their own investments. Consistent with the theory of investment under uncertainty, we find that U.S. domestic firms are less responsive to investment opportunities as expectations of leaders’ shifting increase. This reduced responsiveness is concentrated among firms facing higher investment irreversibility and those whose market leaders provide less transparent geographic disclosures. Our findings identify a novel spillover cost of income shifting and suggest that policies enhancing the transparency of multinational firms’ geographic reporting or constraining income shifting could help improve domestic firms’ investment decisions.